Li Ziqi's Chinese Idyllic Dream - Analysis of the Symbolic Characteristics of Vernacular Culture from Symbolic Aggregation Theory/Semiotic Theory - Yanrong Qu (TAMA: Journal of Visual Arts, 2025)
Li Ziqi is a video blogger who shares his daily life in the Chinese countryside on YouTube. Within his videos, he covers typical vernacular cultural topics such as Chinese countryside life, traditional food preparation, family records, and Chinese seasonal life. The popularity of Li Ziqi on YouTube highlights the cultural interoperability of human idyllic dreams. This study aims to use Roland Barthes' semiotic approach to analyze the invisible and explicit messages in the videos of Li Ziqi's channel and explain the symbolic features of vernacular culture embedded behind them.